A new species of Branchinecta (Crustacea: Branchiopoda: Anostraca) from the Argentinian Tierra del Fuego - Cohen, Rosa Graciela (Zootaxa, 2008)
Branchinecta fueguina, a new species of fairy shrimp, was found together with B. granulosa in a temporary pond beside Laguna de los Cisnes, 53°47’12’’S, 67°46’55’’W, Tierra del Fuego, Antártida e Islas del Atlántico Sur Province (Argentina). The male second antennal basal article has a proximal, anteriomedial auriculate welt, covered with sensory setae and a hanging posteriomedial ornamented apophysis bending abruptly anteriorly with a rounded apex. Distally, the basal article has a longitudinal medial crest, proximally produced into a blunt posteriomedially directed point. The distal article is strongly rotated, articulating almost perpendicular to the basal article. The anterior surface of the article is triangular, from its proximal joint to the broadly explanate apex. Distally, the broadened article bends anteriorly forming a complex three-lobed apex. The peculiar joint with the basal article and the distal article shape are unique in the genus.